Cetyltrimethylammonium chloride influence on silica optical fiber strength - El Abdi, R.; Rujinski, A.D.; Boumbimba, R.M.; Poulain, M. (Фізико-хімічна механіка матеріалів, 2013)
The evolution of silica optical fibers strength aged in cetyltrimethylammonium chloride
solution (CTAC) are investigated. The mechanical behaviour of silica coated and naked
fibers in contact with CTAC solution at different concentrations is studied. Result analysis
proves that the immersion in CTAC drastically decreases the fiber strength and specially
near the critical micelle concentration point (CMC). Beyond CMC point, a small increase
of fiber strength is analyzed and commented. Based on analysis of aged fiber surface
morphology obtained from Scanning Electron Microscopy, the damage extent on fiber
core and polymer coatings is observed. Досліджено еволюцію міцності оптичного кварцового волокна під час
старіння у розчині хлористого цетилтриметиламонію (ХЦТА) та механічні властивості
волокон з кварцовим покривом і без нього, що контактують з розчином ХЦТА за різних
концентрацій. Результати аналізу підтвердили, що занурення трубок у ХЦТА значно погіршують міцність волокна, особливо біля точки критичної концентрації міцел (ККМ).
Виявили незначне зростання міцності волокна поза точкою ККМ. На основі аналізу сканівною електронною мікроскопією морфології поверхні зістарених волокон виявлено пошкодження ядра волокна та полімерного покриву. Исследовано эволюцию прочности оптического кварцевого волокна во
время старения в растворе хлористого цетилтриметиламония (ХЦТА) и механические
свойства волокон с кварцевым покрытием и без него, что контактируют с раствором
ХЦТА при разных концентрациях. Результаты анализа подтвердили, что погружения трубок в ХЦТА значительно ухудшают прочность волокна, особенно около точки критической концентрации мицел (ККМ). Обнаружили незначительный рост прочности волокна
вне точки ККМ. На основе анализа сканирующей электронной микроскопией морфологии
поверхности состаренных волокон выявлены повреждение ядра волокна и полимерного
покрытия.